La importancia de la educación ambiental ante la problemática actual - Martínez Castillo, Róger (2010)
The dominant development system with its neoliberal policies and market-centered approaches contribute to aggravate the socio-environmental problems, under the context of the globalization of the market. For that reason, the concern about the sustainable development of the environment makes highly necessary the structuring of an environmental education that forms and informs about this problem. As a result, environmental education constitutes the educational process that deals with the relation between the human being and his/her environment (natural and man-made) and with itself, as well as the effects caused by this relation. In this way, environmental education must constitute an integral process, which plays its role throughout the whole teaching and learning intertwinement. For this reason it is necessary to establish an educational process that examines the relation of any topic or human being activity, within an analysis of the importance or incidence on social life, as it is the pedagogical part and its political essence.